PROFESSIONAL TEACHER AND CLASSROOM MANAGEMENT IN PRIMARY SCHOOL - Naeklan Simbolon (ELEMENTARY SCHOOL JOURNAL PGSD FIP UNIMED, 2015)
Teachers are agents of renewal that acts as a facilitator of learning and are responsible for the achievement of learning outcomes of students. The success of students is determined by the strategy undertaken by the teacher. Teachers are required to improve the process of learning in the classroom so that learners are more eager to learn. Teaching is not just a transfer of knowledge to students, but a number of behaviors that will become the property of the learner. The use of approaches, methods, strategies, techniques and learning media are part of the learning management that should be implemented by the teacher in the classroom. Professional teacher acts as a manager in a class and masters class management. Keywords:Teacher, professional, classroom,management.